2018
DOI: 10.1016/j.ijbiomac.2018.04.167
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray-assisted encapsulation of caffeine in alginate microhydrogels

Abstract: One of the major challenges with microencapsulation and delivery of low molecular weight bioactive compounds is their diffusional loss during storage and process conditions as well as under gastric conditions. In an attempt to slow down the release rate of core material, electrospray fabricated calcium alginate microhydrogels were coated with low molecular weight and high molecular weight chitosans. Caffeine as a hydrophilic model compound was used due to its several advantages on human behavior especially inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…In the ES process, there are several ways of collecting the MPs, such as on stainless steel plates [34], stainless steel plates coated with an aluminum foil [28], aluminum foils [40], an aluminum plate [63], beakers or Petri dishes containing different solvent such as MeOH or EtOH [39], Polysorbat 80 surfactant (Tween 80) [39], phosphate buffer or citrate buffer [35], solutions containing 2% (w/v) CaCl 2 , etc. [64]. In this context, Faramarzi et al investigated the production of MPs of PLGA in different collection baths [39].…”
Section: Types Of Collectorsmentioning
confidence: 99%
“…In the ES process, there are several ways of collecting the MPs, such as on stainless steel plates [34], stainless steel plates coated with an aluminum foil [28], aluminum foils [40], an aluminum plate [63], beakers or Petri dishes containing different solvent such as MeOH or EtOH [39], Polysorbat 80 surfactant (Tween 80) [39], phosphate buffer or citrate buffer [35], solutions containing 2% (w/v) CaCl 2 , etc. [64]. In this context, Faramarzi et al investigated the production of MPs of PLGA in different collection baths [39].…”
Section: Types Of Collectorsmentioning
confidence: 99%
“…The gelation phenomenon is triggered when calcium ions react with the free carboxyl moieties present in the alginate structure by ion crosslinking, forming hydrogels, and thus trapping the bioactive substances [7,9]. The extrusion method mostly produces capsules with diameters of several mm dominantly controlled by rheological properties of the polymer solution and the extrusion system tip diameter [10,11]. To fabricate capsules by ionic gelation in a more controllable manner, techniques such as the electrospraying (electrohydrodynamic atomization) method have gained great attention, but traditional extrusion techniques continue to be used to assess the gelation capacity of different coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…These results also indicate that the structure of capsules must be different depending on the production method. In this regard, Nikoo et al (2018) reported for capsules prepared by EM that the electrostatic interaction between wall materials provides an effective barrier against, in this case, the release of caffeine, along with a decrement of the swelling of particles. In another study, the swelling behavior has been related to pH, solubilization, and degradation of wall materials (Bajpai & Sharma, 2004;Xie et al, 2016), where at higher pH a larger effect was observed, as a result of diffusion of calcium ions, which would lead to higher liberation of the capsule enclosed materials.…”
Section: Fermentation Step (Ph Stress)mentioning
confidence: 99%
“…It is biocompatible, biodegradable, and hydrophilic (Dima et al., 2016) and has been used in the encapsulation of several enzymes (tyrosinase, urease). However, its network structure has open pores (Nikoo et al., 2018), which leads to an inefficient retention of smaller molecular compounds (Hao et al., 2020), including enzymes, and a rapid initial release in aqueous environments. Therefore, to control or delay the release rate, it is necessary to strengthen its structure using secondary biopolymers, thus emerging the need to combine it with other biopolymers.…”
Section: Introductionmentioning
confidence: 99%